Strategi Guru PAI Untuk Menjadi Teladan Bagi Siswa dalam Menanamkan Nilai Kejujuran Di Smk Wahid Hasyim Pucuk - Muhammad Fatkhur Rozak; Novita Sari; Isfaiyatul Muhimmah (AJER: Advanced Journal of Education and Religion, 2025)
education is a mandate that must be exceeded on from era to technology. therefore, to gain instructional and coaching desires, the position of the trainer could be very influential so that the instructor will become one of the factors that maximum determines the success of the studying procedure. Instilling precise behavior as early as viable may be very critical for students. This research goals to determine the techniques of Islamic religious schooling instructors to become role models in instilling the values of honesty at HASYIM ASY'ARI PUCUK Vocational school. The technique used is qualitative information series the use of remark, interviews and documentation strategies. The results and conclusions of the research show that the efforts of Islamic spiritual schooling teachers to be exemplary in instilling the values of honesty at HASYIM ASY'ARI PUCUK Vocational college by means of presenting excellent examples and asking students to use them in everyday existence each inside the school surroundings and within the network . PAI teachers act as supervisors, mentors, function fashions, and givers of punishment and rewards